Potential role of intermittent fasting on decreasing cardiovascular disease in human immunodeficiency virus patients receiving antiretroviral therapy - Gnoni, Martin (2021)
Cardiovascular disease (CVD) has become one of the commonest causes of comorbidity and mortality among People living with human immunodeficiency virus (HIV) (PLWH) on antiretroviral therapy (ART). Nearly 50% of PLWH are likely to have an increased risk of developing CVD, including coronary heart disease, cerebrovascular disease, peripheral artery disease and aortic atherosclerosis. Aside from the common risk factors, HIV infection itself and side effects of antiretroviral therapy contribute to the pathophysiology of this entity. Potential non-pharmacological therapies are currently being tested worldwide for this purpose, including eating patterns such as Intermittent fasting (IF). IF is a widespread practice gaining high level of interest in the scientific community due to its potential benefits such as improvement in serum lipids and lipoproteins, blood pressure (BP), platelet-derived growth factor AB, systemic inflammation, and carotid artery intima-media thickness among others cardiovascular benefits. This review will focus on exploring the potential role of intermittent fasting as a non-pharmacological and cost-effective strategy in decreasing the burden of cardiovascular diseases among HIV patients on ART due to its intrinsic properties improving the main cardiovascular risk factors and modulating inflammatory pathways related to endothelial dysfunction, lipid peroxidation and aging. Intermittent fasting regimens need to be tested in clinical trials as an important, cost-effective, and revolutionary coadjutant of ART in the fight against the increased prevalence of cardiovascular disease in PLWH.